ISOLATION, CHARACTERIZATION, AND BIOLOGICAL ACTIVITY EVALUATION OF BIOACTIVE COMPOUNDS FROM HERBAL PLANTS AS DRUG CANDIDATES - Saeful Amin; Asri Ainul Qolbiah; Dania Alawiyah; Shaila Juliya Pralita (PT. Radja Intercontinental Publishing, 2026)
Research on herbal plants in the field of medicinal chemistry aims to explore the potential of bioactive compounds as drug candidates. Herbal plants are known to contain secondary metabolites such as flavonoids, alkaloids, and phenolic compounds that exhibit various biological activities. This study aims to evaluate the potential of active compounds derived from herbal plants through a medicinal chemistry approach, including isolation, characterization, and biological activity evaluation based on literature studies. The method used in this study was a literature review of relevant scientific journals, including publications from lecturers and other supporting articles. The results indicate that bioactive compounds from herbal plants possess antioxidant, antibacterial, antidiabetic, and anticancer activities. Furthermore, medicinal chemistry approaches such as structural modification and molecular docking have been shown to enhance the effectiveness and selectivity of compounds toward biological targets. In conclusion, herbal plants have great potential as sources of new drug candidates that can be further developed through medicinal chemistry approaches.